2012
DOI: 10.7763/ijtef.2012.v3.221
|View full text |Cite
|
Sign up to set email alerts
|

Will Final Year Accountancy Students Whistle Blow?A Malaysian Case

Abstract: This paper aims to explore the ethical views of final year accountancy students in Malaysia. Specifically, this study seeks to investigate the final year accountancy students' perception on whistle blowing and the likelihood of blowing the whistle in relation to seriousness of questionable act, gender, race and academic performance. About 150 questionnaires were distributed to final year accountancy students in a public university in Malaysia; however, only 105 questionnaires were usable and completed to be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
2
16
1
1
Order By: Relevance
“…Whistle-blowing telah menarik perhatian dunia saat ini. Banyak perusahaan besar melakukan kecurangan dan akhirnya terungkap dengan bantuan whistle-blowing tersebut (Mustapha dan Siaw, 2012). Di Indonesia, kasus mengenai kecurangan yang akhirnya terbongkar juga terjadi pada institusi pemerintahan.…”
Section: Pendahuluanunclassified
“…Whistle-blowing telah menarik perhatian dunia saat ini. Banyak perusahaan besar melakukan kecurangan dan akhirnya terungkap dengan bantuan whistle-blowing tersebut (Mustapha dan Siaw, 2012). Di Indonesia, kasus mengenai kecurangan yang akhirnya terbongkar juga terjadi pada institusi pemerintahan.…”
Section: Pendahuluanunclassified
“…According to Zimbelman et al (2014), there are several elements for whistleblowing systems to function effectively, anonymity, independence, access, and follow-up. Mustapha & Siaw (2012) states that whistleblowing is a complex process involving personal and organizational factors. According to (Lee & Fargher, 2018), there are two types of whistleblowing, namely internal whistleblowing and external whistleblowing.…”
Section: Individual Perception Of Ethical Behavior and Whistleblowingmentioning
confidence: 99%
“…In contrast, Miceli and Near (1988) found that males were more inclined to report wrongdoings than female employees. Other research has suggested that gender is not a significant factor affecting the decision to blow the whistle (Brennan and Kelly, 2007;Mustapha and Siaw, 2012). As the prior research does not reach a consensus, gender is included in the analysis as a control variable.…”
Section: Moralitymentioning
confidence: 99%
“…2.3.5 Seriousness of the wrongdoing. The general consensus is that the more serious the issue, the more likely it is that an individual will blow the whistle (Elias, 2008;Mustapha and Siaw, 2012). However, Brennan and Kelly (2007) specifically consider the relevance of the materiality of the wrongdoing for whistle-blowing by trainee accountants, concluding that a lack of practical experience negated the relevance of the seriousness of the issue under review.…”
Section: Moralitymentioning
confidence: 99%